P229Tranexamic acid and aprotinin: antifibrinolytics in cardiac surgery. (15th July 2014) - Nemeth, BT; Hidi, L; Toth, R; Veres, G; Olah, A; Matyas, C; Merkely, G; Merkely, B; Szabo, G; Radovits, T
Abstract: Purpose: Anti-haemorrhagic drugs are being used to prevent and treat haemorrhagic complications in cardiac surgery. The serine-protease-inhibitor aprotinin is an antifibrinolytic agent that had been used in clinical practice for decades. In 2008, the BART-study revealed its unfavourable effects on postoperative mortality, which led to its withdrawal from the market. Today, the lysine-analogue tranexamic acid (TA) is available for the clinical routine. We compared the effects of aprotinin and TA on postoperative blood loss, hemodynamic, hemostaseologic and inflammatory parameters, using a canine model of cardiopulmonary bypass (CPB). Methods: Beagle dogs were randomized into three groups (n=8/group). Control dogs received placebo, treated groups were given aprotinin or TA. All animals received heparin and underwent 90min of CPB. The weaning from the heart-lung-machine was followed by administration of protamine and 130min of observation. We regularly determined blood loss and coagulation parameters, while hemodynamic parameters were continuously monitored. To assess the systemic inflammatory response induced by CPB, plasma levels of IL-6, IL-8 and TNF-α were determined by ELISA. Results: Compared to control, aprotinin significantly reduced blood loss (105±22ml vs. 41±8ml), while TA was found to be less effective (65±16ml). Regarding hemodynamic and coagulation parameters, no significant difference was detected among the groups. The elevation of proinflammatory cytokine levels during CPB was tendentially decreased by aprotinin, while a significant anti-inflammatory effect was observed in the TA group (TNFα 90min after starting CPB: 5.2±1.2ng/ml control vs. 3.7±0.9ng/ml aprotinin vs. 0.8±0.3ng/ml TA). Conclusions: Compared to aprotinin, TA is less effective in reducing blood loss, but has a stronger anti-inflammatory effect. Our work points out the need for the development of novel pharmacological tools for effective and safe postoperative blood loss reduction.